First report of the genus Tettigonia Linnaeus (Orthoptera: Tettigoniidae: Tettigoniinae) and record of Tettigonia caudata caudata (Charpentier, 1842) from India - Nagar, Rajendra; Swaminathan, R. (Zootaxa, 2017)
The genus Tettigonia Linnaeus (Tettigoniidae; Tettigoniinae) with the type species, Gryllus (Tettigonia) viridissima Linnaeus, 1758 belongs to the tribe Tettigoniini, which is represented by 15 genera and 27 species worldwide (Cigliano et al., 2017). According to the annotated checklist, the subfamily Tettigoniinae includes the only tribe Platycleidini Brunner von Wattenwyl, 1893 with 2 genera and 3 species as reported from India by Shishodia et al. (2010). In a review of Orthoptera from the Eastern Palearctic region, the genus Tettigonia Linnaeus was reported by Storozhenko (1994); additionally, some new species of Tettigonia have been described by Ogawa (2003), Greenwalt and Rust (2014), Chobanov et al. (2014), Sultan et al. (2015) and Storozhenko et al. (2015). The sub-family Tettigoniinae is represented by many species endemic to the Asian part of the Palearctic region. In 1971, Kaltenbach studied the Decticinae of the Palearctic, a subfamily now considered part of Tettigoniinae, comprising 65 genera with 407 species; later, Rentz and Colless (1990) estimated 500 species for Tettigoniinae. Further, Rentz (1985) clarified that these species do not occur in tropical rainforests, but are found in grassland and mixed heath habitats. The shape of pronotum, with a distinct angulated shoulder incision, with the clarities and locations of its transversal sulci, and its short, compressed and depressed structure happens to be a common character for the members of the tribe Tettigoniini. The type genus Tettigonia is long winged; however, considerable variability in the wing length has been reported. Nevertheless, the short tegmina reaching to the end of hind knee is a character often used to separate T. caudata and T. viridissima from T. cantans and T. hispina (Haz, 1969).